Methodological aspects of teaching translation and development of professional competencies for international journalists - N. F. Koroleva (Ибероамериканские тетради, 2015)
The article considers the problems of renovation of linguistic education while Spanish is an instrument of professional and multilateral development of student’s personality as a future journalist.